Geostatistical analysis of compositional data - Pawlowsky-Glahn, Vera; Olea, R. A. (Ricardo A.) (Studies in mathematical geosciences., 2004)
1. Introduction. 2. Regionalized Compositions. 3. Spatial Covariance Structure. 4. Concepts of Null Correlation. 5. Cokriging. 6. Practical Aspects of Compositional Data Analysis. 7. Application to Real Data. Summary and Prospects. References. Index.